High output achieved by sliding electrification of an electrospun nano-grating. Issue 41 (14th October 2021) - Zhou, Li-Na; Wu, Jun-Peng; Song, Wei-Zhi; Wang, Xiao-Xiong; Wang, Ning; Yu, Miao; Fan, Zhi-Yong; Ramakrishna, Seeram; Long, Yun-Ze
Abstract : A TENG with a grid structure verified that pressure can change the effective contact area and it can be used as a self-powered code lock. Abstract : The rapid development of flexible and wearable electronics has proposed a trend towards miniaturization, mobility, versatility and artificial intelligence. Triboelectric nanogenerators (TENGs) can make use of micro/nano multi-functional materials to harvest and store energy from the surrounding environment efficiently, which can drive smart portable electronics operating continuously and steadily. The increase in the output power density of the triboelectric nanogenerator requires new designs. In this work, a new grating TENG was proposed, and the two friction layers were fabricated by near-field electrospinning and conventional electrospinning with two parallel electrodes as a collector, respectively. The basic model of the simulation was simplified according to the highly ordered structure and the repeatability of the TENG grating structure. The effect of the effective contact area on the output of the TENG was further proved by fitting the calculation regularity of the two models with the experimental results. At the same time, the effect of the redundant electrode on the output of the TENG was verified by experiments. We found that this nanogenerator can achieve a very high output of 1800 W m −2 due to a more refined grating structure combined with modification of the contact area. The TENG can also be used as a selfpowered sensor to detect mechanical signals, which requires no additional power source to drive it. Meanwhile, the anisotropic nature of the TENG can also be utilized to sense angles, lock devices or encrypt information. This output control technology provides a more effective idea for future output power improvement, that is, a new generation of high-output TENGs can be designed by effectively adjusting the corresponding contact area and electrode area.